2002
DOI: 10.1002/ijc.10743
|View full text |Cite
|
Sign up to set email alerts
|

Rapid turnover of cell‐cycle regulators found in Mirk/dyrk1B transfectants

Abstract: Mirk/dyrk1B is an arginine-directed protein kinase, which functions as a transcriptional activator and mediates serumfree growth of colon carcinoma cells by an unknown mechanism. We now report that turnover of the cdk inhibitor p27 kip1 and the G 1 -phase cyclin cyclin D1 is enhanced in each of 4 Mirk stable transfectants compared to vector control transfectants and Mirk kinase-inactive mutant transfectants. This enhanced turnover is proteasome-dependent and leads to lower protein levels of both p27 kip1 and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
(55 reference statements)
2
18
0
Order By: Relevance
“…8) with only a 20% decrease in p27 mRNA levels (not shown). The minimal effect of Mirk on p27 mRNA levels was also seen by microarray analysis (data not shown) and confirmed our earlier results (21), which showed that Mirk did not modulate the activity of a p27 promoter construct. These data indicated that Mirk plays a post-translational role in maintaining p27 stability in post-mitotic myoblasts as well as NIH3T3 cells.…”
Section: Figsupporting
confidence: 91%
“…8) with only a 20% decrease in p27 mRNA levels (not shown). The minimal effect of Mirk on p27 mRNA levels was also seen by microarray analysis (data not shown) and confirmed our earlier results (21), which showed that Mirk did not modulate the activity of a p27 promoter construct. These data indicated that Mirk plays a post-translational role in maintaining p27 stability in post-mitotic myoblasts as well as NIH3T3 cells.…”
Section: Figsupporting
confidence: 91%
“…3E), accounting for the increased protein abundance. In earlier studies, stable Mirk transfectants of colon cancer cells were shown to exhibit a faster turnover of cyclin D1 (20). Thus, both Mirk depletion (this study) and Mirk overexpression studies showed that Mirk destabilized cyclin D isoforms in colon cancer cells.…”
Section: Mirk Depletion Leads To a Rapid Transit Of G1 In Colon Cancesupporting
confidence: 58%
“…In an earlier study, we had observed that stable overexpression of Mirk in colon carcinoma cells enhanced the turnover of cyclin D1 and the CDK inhibitor p27kip1 (25). These results appeared contradictory and may have resulted from the changes in cell physiology that occur in the presence of elevated expression of an active kinase with many potential cellular targets.…”
Section: Discussionmentioning
confidence: 96%